The Realistic Dilemma and Optimisation Path of Enterprise Digital Management Professional Construction in Vocational Undergraduate Education - Zhu, Wei; Ouyang, Ping (Journal of Educational Research and Policies, 2025)
In the era of digital economy, enterprise digital transformation puts forward new requirements for management talents, and the construction of vocational undergraduate speciality of enterprise digital management faces many challenges. At present, the professional positioning of this major is vague, lack of accurate training standards, curriculum system is out of touch with industrial demand, and interdisciplinary integration is insufficient; the faculty generally lacks digital literacy and industrial practice experience; school-enterprise cooperation is superficial, and lack of in-depth synergistic mechanism and other problems. Aiming at the above realistic dilemmas, this paper puts forward the optimisation paths of adjusting professional orientation, curriculum system, strengthening practical teaching, enhancing the level of teachers and deepening the cooperation between schools and enterprises, with a view to providing references for the professional construction of vocational undergraduate universities.